Effectiveness of Learning Software for Teaching Curricula and their Influence on Developing Thinking Skills and Achievement among Senior Students - Israa Yaseen Abdul-Kareem; Ban Abdul-Rahman Ibraheem; Iman Hamad Shihab (Indian Journal of Forensic Medicine & Toxicology, 2022)
The developments taking place in the world in terms of informational modernity, called the knowledgetechnologyrevolution. Such developments have relied on the use of computers, which have becomethe main sphere of an individual’s life in various educational, sports, and other disciplines, in theservice of the learners. Hence, the importance of research in keeping pace with the educational processof what has happened in the world in terms of inventions and developments, which accommodatetechnology education and becomes an integral part of its curriculum and teaching methods in line withthe characteristics of society.The research problem lies in that many of the teachers adopt the traditional method in teaching thecurricula without updating the teaching method by incorporating the educational software for this courselesson, and the extent of its influence on developing thinking skills and achievement for fourth-stagestudents in the Department of Physical Education and Sports Sciences - College of Basic Education atMustansiriya University that teaches this course in the curriculum of this stage.The researchers concluded that these students are equal in their acquiring of thinking skills and obtaininginformation, concepts, and subjects of the curricula, and there is an association in the achievement testfor the study group.